EARLY LEFT VENTRICULAR REMODELING AFTER AORTIC VALVE REPLACEMENT - Ahmad, Naseem; Shahbaz, Ahmad; Ghaffar, Abdul; Tufail, Zafar; Waheed, Abdul; Khan, Jawad Sajid (Journal of Ayub Medical College Abbottabad, 2007)
Background: Aortic valve disease is associated with eccentric or concentric left ventricular (LV) hypertrophy and changes in the LV mass. The relationship between LV mass and function and the effect of LV remodeling after aortic valve replacement (AVR), in patients with aortic valve disease needs evaluation, that is largely unknown in our population. The aim of this study was to evaluate the effect of AVR on LV remodeling, in patients with aortic valve disease. Methods: Fifty patients with aortic valve disease were studied using transthoracic echocardiography to assess LV mass before AVR and compared with early postoperative changes in the LV dimensions and function. LV mass was studied preoperatively and before discharge in 50 consecutive patients undergoing isolated aortic valve replacement. Results: Out of fifty patients, 47(94%) were male and 03(6%) were female. Mean age of the patients was 40.42 years. 22 (44%) had isolated aortic stenosis (AS), 16 (32%) patients had isolated aortic regurgitation (AR) and 12 (24%) patients had mixed aortic valve disease (MAVD). 02 (4%) patients died. LV mass regression was studied in all the patients. In group A, with aortic stenosis, LV regressed to 69.88 gm (mean) with maximum of 156.88 gms and minimum of 0.00 gms (SD 43.67 gms, p value = 0.001). In group B, with aortic regurgitation, LV mass regressed to 203.96 gms (mean) with maximum 453.79 gms and minimum of 45.65 gms (SD 95.33, p value = <0.001). In group C, with mixed aortic valve disease, postoperatively LV mass regressed to 122.94 gms (mean) with minimum 9.57 and maximum of 224.75 gms (SD 69.53, p value = 0.524). Conclusion: There was significant early LV mass regression after aortic valve replacement in patients with pre existing aortic valve disease. However, it was noticed that LV mass regressed in all patients except no significant changes in LV wall thickness (hypertrophy). Keywords: Aortic valve replacements; Left ventricular mass regression; Left ventricular function.